Studi Pendahuluan Potensi Bencana Alam (Geo-Disaster) Di Pulau Bangka - Irvani Irvani; Indra Gunawan (PROMINE, 2015)
The study area is a tin mining region in hundred years, located in Bangka Island, Bangka BelitungArchipelago Province. Identifying geo-disaster potential, in order that to know the the type, spatialdistribution of geo-disaster that caused by geogenic or antropogenic factor. The research is done byobserving all of geo-disaster potential, with geological and geomophological additional condition. Geodisasterpotential is ilustratrated in a map as result of work using geographic information system (GIS)software that is supported from Landsat TM7 analysis. Erosion, sedimentation, lanslide andabration disaster mainly caused by antropogenic factors from tin mining activities and landfarming, butfor dryness, flood, hurricane and earthquake caused by geogenic factors. For flood and dryness alsoinfluenced by antropogenic factor. Dryness, erosion and sedimentation has the large spatialdistribution in Bangka Island.